Impact of parental asthma, prenatal maternal asthma control, and vitamin D status on risk of asthma and recurrent wheeze in 3‐year‐old children. Issue 4 (3rd January 2019) - Mirzakhani, Hooman; Carey, Vincent J.; Zeiger, Robert; Bacharier, Leonard B.; O'Connor, George T.; Schatz, Michael X.; Laranjo, Nancy; Weiss, Scott T.; Litonjua, Augusto A.
Abstract: Background: While familial clustering of asthma is known, few studies have reported on the relative roles of paternal and maternal asthma and the role of maternal asthma control in pregnancy on the risk for asthma in the child. Objective: We aimed to investigate the relative roles of paternal asthma, maternal asthma, and maternal asthma control during pregnancy on the risk of asthma or recurrent wheeze in 3‐year‐old children and how prenatal and cord blood vitamin D status might affect this risk. Methods: Data from 806 women, their partners (biologic fathers of the infants), and their children participated in the Vitamin D Antenatal Asthma Reduction Trail (VDAART, clinicaltrials.gov identification number NCT00920621) were used for this cohort analysis. The parental report of physician‐diagnosed asthma or recurrent wheeze in offspring was the main outcome. Weibull regression models for interval‐censored event times were used to estimate the main variables of interests and additional covariates on the outcome. Results: The highest risk was observed among children with both parents being asthmatic relative to non‐asthmatic parents (aHR = 2.30, 95% CI: 1.35‐3.84), and less so if only the mother was asthmatic (aHR = 1.70, 95% CI: 1.17‐2.40). In the subset of children born to asthmatic mothers, the risk for asthma was higher in those who were born to mothers whose asthma was uncontrolled (aHR = 1.60, 95% CI: 1.02‐2.54). Children whose mothers had sufficient vitamin D status (25Hydroxyvitamin D ≥ 30 ng/mL) at early and late pregnancy and had cord blood vitamin D sufficiency demonstrated a lower risk of asthma/recurrent wheeze than children who had insufficient cord blood vitamin D status at birth (aHR = 0.47, 95% CI: 0.27‐0.83). Conclusion and Clinical Relevance: Careful attention to maternal asthma control, monitoring vitamin D status, and correcting insufficiency at early pregnancy and maintaining the sufficiency status throughout pregnancy have potential preventive roles in offspring asthma or recurrent wheeze.